Media In Election Processes - Piechota, Grazyna (Communication Today, 2025)
The politician does not want to be just a subject exposed to the political arena any longer, who is becoming well-known and recognizable thanks to political advertising. The politician is getting more active in the ﬁeld of com-munication processes aimed at creating a new image of the politician, whom the voters know not just from the traditional media but also from their direct contact with the environment and passing his or her views on many subjects e.g. politics, social issues or economy. At the same time, political marketing processes are gradually replaced by political public relations processes, and the one-way direction of the message, which is character-istic of marketing communication, seems to be systematically replaced by the two-way communication, which is typical for the public relations processes. Progressing development of the social media, such as Internet blogs, Facebook, Twitter, as well as the development of political public relations, inﬂuence the changes in both: perceiv-ing the role of the traditional media in the election processes and political communication and in the co-relation between the traditional media and the social media. Social media are more likely to be regarded as being not only complementary to the traditional media, or the brand-new communication tool, but even being an alternative to the traditional media.